Nonlinear Analysis of Reinforced Geopolymer Concrete Beams - Karen Chong; Benny Suryanto; Asdam Tambusay; Priyo Suprobo (Institute of Research and Community Outreach - Petra Christian University, 2022)
To decarbonise the current construction sector and meet the global net-zero target, there is a pressing need to develop an environmentally friendly alternative to Portland cement concrete. Alkali activated and geopolymer concrete have much to offer in this regard. At present, however, there is limited study on the behaviours of alkali activated structural members, particularly on flexural members, which encompass most practical design situations. This paper presents a database of 37 tests on slender alkali activated and geopolymer concrete beams available in the literature, with the aim to investigate the flexural strengths of this alternative concrete when used as a structural member. In addition, the results of nonlinear finite element analyses on fourteen reinforced geopolymer concrete beams are presented to highlight key influencing factors governing the behaviour and failure of flexural members. Of particular interest is to study the influence of reinforcement ratio, compressive strength, and material brittleness on the overall strength and ductility. Overall, it is shown that the flexural response of geopolymer concrete beams under short-term loading is comparable to that of ordinary reinforced concrete beams.